Silicate melt inclusions in the new millennium: A review of recommended practices for preparation, analysis, and data presentation - Rose-Koga, E.F.; Bouvier, A.-S.; Gaetani, G.A.; Wallace, P.J.; Allison, C.M.; Andrys, J.A.; Angeles de la Torre, C.A.; Barth, A.; Bodnar, R.J.; Bracco Gartner, A.J.J.; Butters, D.; Castillejo, A.; et al. (Chemical geology, 2021)
Mineral-hosted melt inclusions have become an important source of information on magmatic processes. As the number of melt inclusion studies increases, so does the need to establish recommended practice guidelines for collecting and reporting melt inclusion data. These guidelines are intended to ensure certain quality criteria are met and to achieve consistency among published melt inclusion data in order to maximize their utility in the future. Indeed, with the improvement of analytical techniques, new processes affecting melt inclusions are identified. It is thus critical to be able to reprocess any previously published data, such that reporting the raw data is one of the first “recommended practices” for authors and a publication-criteria that reviewers should be sensitive to. Our guidelines start with melt inclusion selection, which is a critical first step, and then continue on to melt inclusion preparation and analysis, covering the entire field of methods applicable to melt inclusions. In March of 2000, a melt inclusion workshop was held at the Chateau de Sassenage in Grenoble and a companion issue of Chemical Geology entitled “Melt Inclusions at the Millennium” was published. Erik Hauri was heavily involved with the meeting and contributed two landmark papers to the topical issue of Chemical Geology on the use of secondary ion mass spectrometry to analyze volatiles in melt inclusions. When the melt inclusion community re-convened at Woods Hole Oceanographic Institution (WHOI) in August of 2018, we were saddened that Erik was unable to join us due to his failing health. Less than a month later came the devastating news of his passing at only 52 years of age. In recognition of his incredible contributions to science in general and to the in situ analysis of melt inclusions in particular, the participants and organizers of the WHOI melt inclusion workshop dedicate this collegial paper to Erik Hauri, our colleague, mentor and friend. Thank you Erik.